Turkey’s Nuclear Energy Ambitions: Past Efforts, Present Strategies, and Future Directions - Muhammed Cihat Mercan; Ali İhsan Aygün (Düzce Üniversitesi Teknik Bilimler Dergisi)
Nuclear power plants, popularized by the promise of decreasing dependency on foreign resources and providing supply security, meet 10% of the world’s energy needs as of 2023. Having had this desire for a long time, Turkey wants to have a nuclear-installed power of 10,000 MW according to its energy production targets. In this context, Turkey seems close to realizing this de sire of more than half a century with its Akkuyu and Sinop Nuclear Power Plants. Yet, Turkey follows a different path compared to countries with a nuclear past and took its first concrete steps with an intergovernmental agreement signed with Russia. In this study, the main motivation pushing Turkey to this path, the country’s technical capacity, and its strategy are evaluated. Besides that, the current and possible prospective hazards are indicated. In addition, the contribution of these plants to meet the electricity demand as well as reducing dependency on external resources and the current account deficit have been examined. The study, which also includes a SWOT analysis, predicts that Turkey's intergovernmental agreement-based initiative will serve as an important reference for other future initiatives.